Lemierre Syndrome: A Meta-analysis - Gore,Mitchell R. (2020)
Abstract Introduction Lemierre syndrome, or postpharyngitis anaerobic sepsis, is an infrequent but life-threatening infection that often involves thrombosis of the internal jugular vein. The role of anticoagulation in addition to antibiotics and surgical treatment remains uncertain. Objectives 1) To perform a meta-analysis on outcomes and treatment of Lemierre syndrome; and 2) to evaluate the effect of anticoagulation in Lemierre syndrome on vessel recanalization and on mortality. Data Synthesis A Pubmed database search was conducted using the keywords Lemierre syndrome. A total of 427 studies were identified and reviewed. Data were extracted on patient demographics, treatment type including use and type of anticoagulation, type of antibiotics, presence and location of vessel thrombosis, presence of cranial neuropathies, recanalization of thrombosed vessels on follow-up imaging, organisms isolated on wound or blood cultures, and mortality. The primary outcome variables examined were the effect of anticoagulation on vessel recanalization and mortality. After the review, 359 studies totaling 394 patients between 1990 and 2017 had partial or complete data that could be analyzed. In total, 50 patients had sufficient data on the effect of anticoagulation on vessel recanalization, and 194 had sufficient data on the effect of anticoagulation on mortality. The odds ratio for anticoagulation and vessel recanalization was 1.6 (95% confidence interval = 0.3 to 9.4; p= 0.6). The odds ratio for anticoagulation and death was 0.6 (95% confidence interval = 0.1 to 2.9; p= 0.5). Conclusion The present meta-analysis did not demonstrate a statistically significant effect on vessel recanalization or mortality for patients treated with anticoagulation versus patients not anticoagulated in the Lemierre syndrome literature.